Mathematical Justification Studies in Mathematics Education: An Evaluation of Studies between 2007 and 2016 - YILMAZ, Yasemin; YAMAN, Hakan; AYVAZ, ÃœlkÃ¼; MERSÄ°N, Nazan; DURMUÅž, Soner (Malikussaleh Journal of Mathematics Learning (MJML), 2019)
In this study, it was aimed to evaluate the mathematical justification studies in mathematics education between 2007 and 2016. In the study, 31 theses and articles about mathematical justification in mathematics education were analyzed by means of determined databases. In the literature review, the studies were classified according to the method, the study group, the mathematics subject, and the time frame of ten years. As a result of study, mathematical justification studies in mathematics education were carried out mostly in 2009, 2010 and 2016. As a study group, examined studies are composed mostly of students. As a method, qualitative method was used mostly. The tasks related to justification at three different levels of education were included. According to primary, middle and high school levels, the most common areas of learning for which mathematical justification tasks take place are numbers and operations, algebra and numbers and algebra, respectively.